Magic Realism in Rabindra Sameer's Mrityuko Aayu - Subedi, Yubaraj (Journal of Janta Multiple Campus, 2024)
This article analyzes the novel Mrityuko Aayu in the light of Magic Realism. Applying magic realism is methodological approach for critical analysis of the novel in this article. It follows interpretive textual analysis. Free translation has been used while taking the citation from the novel. I have drawn the conclusion that the novel is a magic realist novel as it has introduced innovative style of narrating the story. The story begins from the death of the protagonist, but he is capable of seeing everything even after the death. It has blended mundane and supernatural, ordinary and extraordinary and real and fantastical elements in an unquestionable way. The novel's extracts are analyzed within five parameters that include fantastical elements, real world setting, incorporation of myth, meta-fiction and social/ political critique. Even after the death of the protagonist, the story moves ahead from the spirit's perspective. The spirit is capable of seeing, feeling and experiencing everything. The readers accept all such actions and happenings as normal without questioning the reliability of them and feel sorry for his painful and pathetic condition. Therefore, the writer is successful in using magic realism in the novel. It is hoped that this article will encourage researchers to study other works of fiction from the point of view of Magic Realism.